1993
DOI: 10.1073/pnas.90.22.10663
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and linguistic differentiation in the Americas.

Abstract: The relationship between linguistic differentiation and evolutionary affnities was evaluated in three tribes of the Pacific Northwest. Two tribes (Nuu-Chah-Nulth and Beila Coola) speak Amerind languages, while the language of the third (Haida) belongs to a different linguistic phylumNa-Dene. Construction of a molecular phylogeny gave no evidence of dustering by linguistic affiliation, suggesting a relatively recent ancestry of these linguically divergent populations. When the evolutionary affinities of the tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(93 citation statements)
references
References 16 publications
4
86
0
3
Order By: Relevance
“…These exceptions appear to correspond to either rare cases of language replacement or genetic admixture between two linguistically distinct populations (Cavalli-Sforza 1997; Chu et al 1998) or cases in which the underlying classi¢cation of language variation remains uncertain (Ward et al 1993;Monsalve et al 1999). Thus, there appears to be a real di¡erence between humans and birds in the degree of coevolution of genetic and cultural traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These exceptions appear to correspond to either rare cases of language replacement or genetic admixture between two linguistically distinct populations (Cavalli-Sforza 1997; Chu et al 1998) or cases in which the underlying classi¢cation of language variation remains uncertain (Ward et al 1993;Monsalve et al 1999). Thus, there appears to be a real di¡erence between humans and birds in the degree of coevolution of genetic and cultural traits.…”
Section: Discussionmentioning
confidence: 99%
“…For traditional human societies there is mounting evidence that language variation is often highly correlated with variation in neutral genes, suggesting that transmission of language has been primarily vertical (i.e. from parents to o¡spring) Piazza et al 1995;Cavalli-Sforza 1997) although some exceptions have been noted (Ward et al 1993;Chu et al 1998;Monsalve et al 1999). Conversely, studies of male song in oscine songbirds have generally not found a strong association between vocal and genetic variation (Kroodsma et al 1985;Fleischer & Rothstein 1988;Payne & Westneat 1988;Lougheed & Handford 1992;Catchpole & Slater 1995) suggesting that horizontal or oblique transmission (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Linguists agree that population fissions and range expansions play an important role in the generation of linguistic diversity (8)(9)(10). The correlation between patterns of linguistic and genetic variation has been studied by many researchers in different world regions with mixed positive (11)(12)(13)(14) and negative (15)(16)(17) findings. Regional differences in population history are likely to explain some of the discrepant results.…”
mentioning
confidence: 99%
“…This difficult situation calls for an efficient phylogenetic analysis to enhance the usefulness of ancient DNA data. Recently a large number of nucleotide sequences, especially for the hypervariable region I of the control region, have been deposited in the DDBJ/EMBL/GenBank International Nucleotide Sequence Database (e.g., Vig ilantet al, 1991;Di Rienzo and Wilson 1991;Ward et al, 1991Ward et al, , 1993Shields et al, 1993;Batista et al, 1995;Redd et al, 1995;Sykes et al, 1995;Betty et al, 1995;Kolman et al, 1996;Comas et al, 1996;Horai et al, 1996). In this study, we re trievedthese human mtDNA nucleotide sequences from the DDBJ/EMBL/GenBank database, in order to examine precision of the phylogenetic analyses using the mtD NAshort sequence.…”
mentioning
confidence: 99%